Pengaruh Konten Kartun Pada Akun Instagram @jokowi Terhadap Citra Jokowi - Aufiyah, Kiara; Prisgunanto, Ilham (Prisani Cendekia Institute, 2023)
The model of communicating by utilizing the internet as a technical and physical medium is a new phenomenon in the communication process that has occurred between humans since the end of the 20th century and has become a fundamental part of society, education, industry, and government. This is also done by the highest figure in the government, President Joko Widodo. He often uses cartoons in his social media content as his communication style. This study aimed to determine the strength of the cartoon narrative on Instagram @Jokowi social media and to determine the level of understanding of netizens towards the figure of Joko Widodo. The research method used is a quantitative approach. Cartoon content contained in the @jokowi Instagram account has an influence of 50,7% on Jokowi's image, while the rest is influenced by other factors not included in this study by 43%. In the t-test or partial results, Cartoon Content has a significant positive effect on Jokowi's Image. The calculated t value of 10.979 is greater than the t table value of 1.660, which means that the Ha hypothesis is accepted that cartoon content on Instagram @jokowi affects Jokowi's image. Therefore, Jokowi's communication team, through his Instagram account, is expected to expand the strategies that have been carried out to improve the quality of his image.